The role of circular Ribonucleic Acid in preeclampsia: a literature review - William Alexander Setiawan; A.A. Gde Marvy Khrisna Pranamartha (Indonesian Journal of Perinatology, 2020)
Circular RNAs (circRNAs) are non-coding RNAs with a covalently closed circular structure that present in a variety of organisms. The circRNAs are more stable and durable than linear RNAs due to incompatibility with the RNases. Recent studies have shown that circRNAs are expressed differently at the mother-fetal interface of women with preeclampsia compared to women with normal pregnancy. Although the evidence showed that circRNAs mediate various pathological processes in pregnancy, the mechanism of action is still unclear. In this paper, we provide a highlight of the current state of knowledge about circRNAs, its relation to preeclampsia, and the potential applications as preeclampsia biomarkers.